Assessment of Subclinical Manifestations of Atherosclerosis of Coronary and Peripheral Arteries and Bone Strength Parameters in Women - I. A. Skripnikova; M. A. Kolchina; O. V. Kosmatova; M. A. Myagkova; V. E. Novikov; O. Yu. Isaykina; O. M. Drapkina (Столичная издательская компания, 2020)
Aim. To study associations between calcification of the coronary arteries (CA), the state of the peripheral vascular wall and bone strength indices.Material and methods. In a cross-sectional study were included 200 women at the age 45-69 y.o. who were observed on an outpatient basis and signed informed consent. A survey was conducted on the presence of cardiovascular risk factors and the risk of fractures. The intima-media thickness (IMT), the presence and number of atherosclerotic plaques (AP) were studied using duplex scanning. Pulse wave velocity (PWV), augmentation index (AI) were measured by applanation tonometry. The presence of calcium deposits in coronary vessels was determined by multispiral computed tomography (MSCT) using the Agatston index. The bone mineral density (BMD) of the spine, hip neck (HN) and proximal hip (PH) was measured using double energy x-ray absorptiometry. The marker of bone resorption C-terminal telopeptide of type-1 collagen (СТх) was determined in blood serum by the β-crosslaps method.Results. There was a positive correlation between the parameters of vascular stiffness, subclinical atherosclerosis of peripheral vessels and CA calcification: AI and calcium index (r=0.25, p<0.05), IMT and calcium index (r=0.23, p<0.05), presence of AP and calcium index (r=0.26, p<0.05). The PWV increased as the calcium index increased, but the correlation remained at the trend level. Women with low bone mass had higher PWV (p<0.05), AI (p<0.01), IMT (p<0.02), CTx level (p<0.001) and a higher number of AP than those with normal BMD. CTx was inversely correlated with PWV and calcium index (p<0.05). Based on multivariate linear regression analysis (adjusted for age, menopause duration, low body weight, smoking factor and total cholesterol) the independent nature of the relationship between the Agatstone index and BMD in all the measured parts of the skeleton, between AI and BMD of HN, and between IMT and BMD of HN was confirmed. The relationship between the marker of bone resorption CTx and BMD of the spine and PH remained highly reliable.Conclusion. The correlation of stiffness indices and subclinical atherosclerosis of peripheral arteries, which is a predictor of high risk of cardiovascular events, allows to suggest an important role of changes in the peripheral vascular wall in increasing cardiovascular risk. A decrease in BMD and an increase in the marker of bone resorption, associated with an increase in indices of vascular stiffness and subclinical atherosclerosis and, especially, CA calcification, allows us to think about the common mechanisms of development and progression of atherosclerosis and osteoporosis. Therefore, early examination of women with a high cardiovascular risk, assessed by the SCORE scale, after 45 years and before menopause to detect vascular rigidity and the presence of subclinical atherosclerosis, and performing x-ray densitometry for individuals with changes in these indices will allow stratify the risks of atherosclerosis and osteoporosis complications and recommend preventive use of drugs that reduce vascular rigidity and increase BMD.